2021
DOI: 10.1371/journal.pntd.0009861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, intensity and associated risk factors of Schistosoma mansoni infections among schoolchildren around Lake Tana, northwestern Ethiopia

Abstract: Background Schistosomiasis is one of the widely distributed neglected tropical diseases. It is a serious public health problem in sub-Saharan Africa. The disease is highly prevalent and widely distributed in Ethiopia due to suitable environmental factors and human activities. The prevalence and infection intensity varied from locality to locality in the country. This study aimed to assess the prevalence and intensity of S. mansoni infection and associated risk factors among schoolchildren around Lake Tana. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
6
3
Order By: Relevance
“…This results may be due to that; some community members refuse to receive drugs during mass administration therapy (or may be due to drug resistance or malabsorption). Our ndings in contrast to studies conducted in Ethiopia which found that the prevalence of S. mansoni was 35.7% and only 8.9% of the study participants had a heavy intensity of infection (38,39). The variations in community water contact activities could easily account for these results.…”
Section: Discussioncontrasting
confidence: 99%
“…This results may be due to that; some community members refuse to receive drugs during mass administration therapy (or may be due to drug resistance or malabsorption). Our ndings in contrast to studies conducted in Ethiopia which found that the prevalence of S. mansoni was 35.7% and only 8.9% of the study participants had a heavy intensity of infection (38,39). The variations in community water contact activities could easily account for these results.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the infection status of Biomphalaria snails around Lake Tana has not been investigated. A recent evidence showed a high prevalence (35%) of S. mansoni infection in humans 7 in the study area despite the ongoing deworming program. In the present study it was hypothesized that there might be a high-level of Biomphalaria snails infected with S. mansoni around Lake Tana.…”
Section: Introductionmentioning
confidence: 86%
“…It is estimated that 85–95% of the global schistosomiasis are in sub-Saharan Africa with the highest prevalence among school-aged childre 3 , 4 In Ethiopia, the prevalence of schistosomiasis could reach as high as 90% in some localities, particularly for Schistosoma mansoni 5 . Although Ethiopia launched a school-based deworming program in 2015 to control schistosomiasis 6 , the prevalence of the disease is still high in several localities 7 – 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The remaining stool sample from Kato–Katz's thick fecal smear was processed using Ritchie's concentration technique [ 29 ]. The detailed procedure of Ritchie's concentration used in this study was described elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%